Temperature effects on vision measurement system in long-term continuous monitoring of displacement. (December 2017) - Zhou, H.F.; Zheng, J.F.; Xie, Z.L.; Lu, L.J.; Ni, Y.Q.; Ko, J.M.
Abstract: Videogrammetry has been recognized as a promising method for monitoring the dynamics of wind turbines. On the way forward, the environmental effects on the measurement accuracy of the videogrammetry are key issues should be solved. This study therefore carried out an investigation into the temperature-induced measurement error of the videometric technique in long-term continuous monitoring of displacement. First, videometric measurement tests specifically targeted for improving the applicability of the videogrammetry to wind turbine blade monitoring were conducted. Making use of the measurement data, the characteristics of the temperature-induced measurement errors were obtained by examining them as a whole as well as their wavelet decomposed components. Comprehensive correlation analyses were performed to quantify the degree of correlation between measurement error and temperature change. It is found that the vertical displacement measurement error and temperature change have a satisfactory linear relationship, while the relationship between horizontal displacement measurement error and temperature change is more scattered. Making use of the unique features of the deformation and thermal expansion of a utility-scale wind turbine blade, it is likely to subtract the temperature-induced measurement error from the measured displacement with the help of the relationship between measurement error and temperature change or a time-frequency approach. Highlights: Videometric tests targeted for improving its applicability to wind turbine. Significant temperature-induced error in videometric displacement monitoring. Temperature of zoom lens is most correlated with displacement measurement error. It is likely to subtract temperature-induced error via a time-frequency approach.